Blackout - Clayton, Dhonielle; Jackson, Tiffany D.; Stone, Nic.; Thomas, Angie (b, 2021)
When a heatwave plunges New York City into darkness, sparks fly for thirteen teenagers caught up in the blackout. A first meeting. Long-time friends. Bitter exes. And maybe the beginning of something new... When the lights go out, people reveal hidden truths, love blossoms, friendship transforms and new possibilities take flight. Six of today's biggest stars of the YA world, Dhonielle Clayton, Tiffany D. Jackson, Nic Stone, Angie Thomas, Ashley Woodfolk, and Nicola Yoon, bring all the electricity of love to a collection of charming, hilarious and heartbreaking tales that shine the brightest light through the dark
Keywords: Romance fiction; Young adult fiction, American; short stories